Sequencing Financial Sector Reforms. (International Monetary Fund, 1991)
Financial sector liberalization can spur economic growth and development, but reforms to liberalize the financial sector can also entail risks if they are not properly designed and implemented. One of the central questions for countries reforming their financial systems is how to sequence the reforms so as to maximize the benefits of liberalization and contain its risks. Edited by R. Barry Johnston and V. Sundararajan of the IMF's Monetary and Exchange Affairs Department, this book attempts to answer this and related questions by drawing lessons from financial sector reforms in selected countries. In particular, the book surveys financial sector reforms in Indonesia, Thailand, and Korea between the mid-1980s and mid-1990s.